Dinamika Dharma Santi Nyepi Di Kodam IX/Udayana - Putu Ayu Sri Kumala Dewi; I Gusti Ngurah Sudiana; I Nyoman Alit Putrawan (Jayapangus Press, 2019)
The life context of a multidimensional and multicultural society requires guidance in safeguarding the universal values of religions. Kodam IX /Udayana is one of the government institutions that routinely implements dharma santi nyepi with various dynamics. This dynamic arose from the differences in the perspective of soldiers and PNS TNI Kodam IX / Udayana. The problems that discussed in this study include: the dynamics of dharma santi nyepi at Kodam IX / Udayana, factors that cause the dynamics of dharma santi nyepi at Kodam IX / Udayana, and the impact of dharma santi nyepi on the performance of soldiers and TNI PNS Hindu at Kodam IX / Udayana. Problem formulation in this study was dissected using the Theory of Social Change, Structural Functional Theory, System Theory, and Symbolic Interactionism Theory. The method used in this study is a qualitative research method. The data collection techniques used include: interviews, observation, and library techniques. The analysis of the data used is descriptive qualitative. The results obtained in this study are 1) The dynamics of the meaning of dharma santi nyepi experience expansion and narrowing. Dynamics The form of implementation of dharma santi nyepi in Kodam IX / Udayana is generally carried out formally and informally. The dharma santi nyepi activity at Kodam IX / Udayana received support in the form of emotional support, instrumental support and informative support. 2) Factors that caused the dynamics of dharma santi nyepi were due to internal factors such as the presence of new innovations, the Udayana Military Command / IX Commander and the Kodam IX / Udayana Military and Civil Servants Authority and external factor such as incidental activities and cultural influences outside Kodam IX / Udayana. 3) The impact of dharma santi nyepi at Kodam IX / Udayana such as increasing faith and piety, increasing nationalism and patriotism, increasing harmony among religious people, and increasing the professionalism of the performance of TNI soldiers and PNS TNI Kodam IX / Udayana.